Ruthenium single atoms implanted continuous MoS2-Mo2C heterostructure for high-performance and stable water splitting. (October 2021) - Hoa, Van Hien; Tran, Duy Thanh; Prabhakaran, Sampath; Kim, Do Hwan; Hameed, Nishar; Wang, Hao; Kim, Nam Hoon; Lee, Joong Hee
Abstract: Merging metal single atoms into a nanostructure is a novel approach to motivate the number and types of active centers for boosting catalytic activities towards both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in water splitting. Herein, we reported a continuous molybdenum sulfide-carbide heterostructure-based nanosheets incorporated with ruthenium atoms (2.02 at%) and shelled over high-conductive 1D titanium nitride nanorod arrays (Ru-MoS2 -Mo2 C/TiN) to form a 3D hierarchical porous material via an effective synthesis strategy. The material with fine-tuned electronic structure and multi-integrated active sites exhibited small overpotentials of 25 and 280 mV at 10 mA cm −2 for HER and OER in 1.0 M KOH medium, respectively. An electrolyzer delivered from Ru-MoS2 -Mo2 C/TiN required an operating voltage of only 1.49 V at 10 mA cm −2, surpassing that of a commercial catalyst-based system as well as earlier reports. The good performance was identified by its enlarged electroactive surface area and superior charge-transfer ability. In addition, theoretical calculations further showed its reasonable density of states near the Fermi level together with optimum adsorption free energy for reactants. The result indicated that the Ru-MoS2 -Mo2 C/TiN on CC is an excellent bifunctional electrocatalyst for hydrogen production by electrochemical water splitting. Graphical Abstract: ga1 Highlights: A continuous Ru-doped MoS2 -Mo2 C heterostructure shelling over 1D TiN is synthesized. Ru-MoS2 -Mo2 C/TiN demonstrates good catalytic activity for both HER and OER. Ru-MoS2 -Mo2 C/TiN-based electrolyzer requires a cell voltage of 1.49 V at 10 mA cm −2 . DFT calculation suggests the optimum DOS and free energies of Ru-MoS2 -Mo2 C for water electrolysis.